Pengembangan E-Modul Berbasis Education For Sustainable Development (ESD) pada Topik Pemanfaatan Logam Bekas sebagai Elektroda Salt Water Battery untuk Melatih Literasi Sains - Nushhi Himmatul A'liyah; Ali Kusrijadi; Hernani (Universitas Garut, 2026)
Scientific literacy is an essential competency in chemistry education; however, its development remains a significant challenge. One of the factors contributing to the low level of scientific literacy is the limited quality of teaching materials used in the learning process. This study aimed to develop and validate an Education for Sustainable Development (ESD)-based e-module on the utilization of waste metal materials as electrodes for salt water batteries to support students' scientific literacy. The study employed the Design and Development Research (DDR) approach, focusing on Product and Tool Research, which consists of four stages: analysis, design, development, and evaluation. The participants included five chemistry teachers involved in the needs analysis stage, three validators (two university experts and one chemistry teacher), and nine twelfth-grade students from a public senior high school in Bandung City who were selected based on their academic achievement for the limited trial. The findings indicate that the developed e-module fulfills the characteristics of a high-quality e-module and meets the criteria for content, presentation, and language feasibility. Furthermore, the module integrates scientific literacy components with the principles of Education for Sustainable Development (ESD), thereby supporting contextual learning that is relevant to students' everyday lives. The validation results confirmed that the e-module is suitable for classroom implementation, with several recommendations for further refinement. The limited trial also demonstrated a positive improvement in students' scientific literacy profiles, with achievement levels ranging from 63% to 96%, which falls within the good category. These findings suggest that the developed ESD-based e-module has the potential to serve as an effective instructional resource for fostering scientific literacy in chemistry learning.Keywords: E-Module, ESD, salt water battery, science literacy